Estudio sobre el uso del agua en los procesos productivos de la corporación ecuatoriana de aluminio Cedal S.A., Planta Latacunga, para el ahorro y uso eficiente. - Armas Sigcha, Milton Enrique (2018)
The Ecuadorian Aluminum Corporation CEDAL SA, enterprise Latacunga, as part of its policy of growth and continuous improvement, framed in the quality of its products, use of its resources, care and protection of the environment, sees the need to conduct the study on the use of water in their productive processes to achieve savings and efficient use. The determination of the use of water in each stage comprised by extraction, treatment and distribution allows to reduce existing losses, to know areas of greater consumption, to demonstrate the current state of the distribution system and the efficiency with which the equipment and elements that make up the system. The diagnosis of the pipe system has been carrying out in the first instance through the process diagram and the pipe flow diagram. It allows, the selection of the strategic zones for the measurement of flows, both in open discharge zones through the appraisal method volumetric, as in the discharge areas closed with the help of ultrasonic flow meter TDS 100-H and the use of water meters. From measurements made in the supply system, the initial balance of water use of the whole plant is made to establish potential consumption, losses and inefficient uses, which lead to the implementation of an action system of improvements for saving and efficient use of water. Before the implementation of the improvement action system, its technical, financial, environmental and institutional viability is analyzed in relation to the expected net benefits. The evaluation and control of the system carried out is based on the established schedule, to carry out the current balance of water use, and demonstrate compliance with the objectives set for this work, reflected in economic savings for the company.